SOCIO – ECONOMIC FACTORS INFLUENCING INSURGENCY ON COWPEA PRODUCTION IN SELECTED LGA’S OF YOBE STATE, NIGERIA - Maimusa, A.; Bose, A. A.; Jibril, S. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study examined the effect of insurgency on cowpea production in Geidam and Gujba Local Government Areas, in Yobe State, Nigeria. A multi-stage sampling techniques was used to select 169 cowpea farmers. Data were collected using structured questionnaire and analysed using both descriptive and inferential statistics. The result revealed that the mean age of cowpea farmers was 38 years. Most (93.0% and 91.7%) of the farmers were male and married with an average household size of 8 persons. The result also showed that the cowpea farmers had average farming experience of 9 years with a mean farm size of 3 hectares. Furthermore, the result showed that mean annual income before and during insurgency were ₦489,053.00 and ₦257,278.00 respectively. The result also showed that 40.2% of the cowpea farmers had never attended formal education. The result revealed that Almost all (96.4%) and majority 72.8% of the farmers confirmed that boko-haram and Kidnappings were the serious forms of insurgency. The major causes of insurgency include: unemployment (91.1%), poor education (82.8%) and poverty (66.3%) among others. The result of regression showed that income during insurgency (-1.763E-6) and sex (-1.117) had negative coefficient and significant (P<0.05 and P<0.01) respectively in influence insurgency. Also, farm size, household size, output during insurgency and farming experience had positive coefficient and significant (P<0.05) in influencing insurgency. The result further disclosed that R – square was 0.631and this was justified by F – value of 3.278 which was significant at P<0.01. The study concluded that, insurgency had adversely affected the livelihood of the farmers in both Local Government Areas. The study recommends that employment opportunities should be given to the youths, credit facilities and grants by government/NGOs, in order to boost the production of cowpea and living standard of the farmers in the study area.